Cold Ionospheric Ions in the Magnetic Reconnection Outflow Region. Issue 10 (19th October 2017) - Li, W. Y.; André, M.; Khotyaintsev, Yu. V.; Vaivads, A.; Fuselier, S. A.; Graham, D. B.; Toledo‐Redondo, S.; Lavraud, B.; Turner, D. L.; Norgren, C.; Tang, B. B.; Wang, C.; et al.
Abstract: Magnetosheath plasma usually determines properties of asymmetric magnetic reconnection at the subsolar region of Earth's magnetopause. However, cold plasma that originated from the ionosphere can also reach the magnetopause and modify the kinetic physics of asymmetric reconnection. We present a magnetopause crossing with high‐density (10–60 cm −3 ) cold ions and ongoing reconnection from the observation of the Magnetospheric Multiscale (MMS) spacecraft. The magnetopause crossing is estimated to be 300 ion inertial lengths south of the X line. Two distinct ion populations are observed on the magnetosheath edge of the ion jet. One population with high parallel velocities (200–300 km/s) is identified to be cold ion beams, and the other population is the magnetosheath ions. In the deHoffman‐Teller frame, the field‐aligned magnetosheath ions are Alfvénic and move toward the jet region, while the field‐aligned cold ion beams move toward the magnetosheath boundary layer, with much lower speeds. These cold ion beams are suggested to be from the cold ions entering the jet close to the X line. This is the first observation of the cold ionospheric ions in the reconnection outflow region, including the reconnection jet and the magnetosheath boundary layer. Key Points: MMS observed cold ionospheric ions deep inside magnetic reconnection outflow Cold ion beams are first observed on the magnetosheath edge of ion jet Cold ion beams in magnetic reconnection are not Alfvenic in the deHoffman‐Teller frame